Role of gender in short- and long-term outcomes after surgery for type A aortic dissection: analysis of a multicentre European registry - Onorati, Francesco; Francica, Alessandra; Demal, Till; Nappi, Francesco; Peterss, Sven; Buech, Joscha; Fiore, Antonio; Folliguet, Thierry; Perrotti, Andrea; Hervé, Amélie; Conradi, Lenard; Dell'Aquila, Angelo M; et al. (European journal of cardio-thoracic surgery : official journal of the European Association for Cardio-thoracic Surgery, 2024)
OBJECTIVES: Gender difference in the outcome after type A aortic dissection (TAAD) surgery remains an issue of ongoing debate. In this study, we aimed to evaluate the impact of gender on the short- and long-term outcome after surgery for TAAD. METHODS: A multicentre European registry retrospectively included all consecutive TAAD surgery patients between 2005 and 2021 from 18 hospitals across 8 European countries. Early and late mortality, and cumulative incidence of aortic reoperation were compared between genders. RESULTS: A total of 3902 patients underwent TAAD surgery, with 1185 (30.4%) being females. After propensity score matching, 766 pairs of males and females were compared. No statistical differences were detected in the early postoperative outcome between genders. Ten-year survival was comparable between genders (47.8% vs 47.1%; log-rank test, P = 0.679), as well as cumulative incidences of distal or proximal aortic reoperations. Ten-year relative survival compared to country-, year-, age- and sex-matched general population was higher among males (0.65) compared to females (0.58). The time-period subanalysis revealed advancements in surgical techniques in both genders over the years. However, an increase in stroke was observed over time for both populations, particularly among females. CONCLUSIONS: The past 16 years have witnessed marked advancements in surgical techniques for TAAD in both males and females, achieving comparable early and late mortality rates. Despite these findings, late relative survival was still in favour of males.
Keywords: retrospektivní studie; tendenční skóre; Humans; lidé; Propensity Score; reoperace; disekce aorty; Retrospective Studies; registrace; lidé středního věku; Treatment Outcome; Sex Factors; sexuální faktory; Middle Aged; Reoperation; Female; Male; výsledek terapie; Europe; aneurysma hrudní aorty; mužské pohlaví; Aged; ženské pohlaví; Postoperative Complications; Aortic Dissection; Evropa; pooperační komplikace; Registries; Aortic Aneurysm, Thoracic; senioři